2021
DOI: 10.3390/biom11030375
|View full text |Cite
|
Sign up to set email alerts
|

Global Proteomics to Study Silica Nanoparticle-Induced Cytotoxicity and Its Mechanisms in HepG2 Cells

Abstract: Silica nanoparticles (SiO2 NPs) are commonly used in medical and pharmaceutical fields. Research into the cytotoxicity and overall proteomic changes occurring during initial exposure to SiO2 NPs is limited. We investigated the mechanism of toxicity in human liver cells according to exposure time [0, 4, 10, and 16 h (h)] to SiO2 NPs through proteomic analysis using mass spectrometry. SiO2 NP-induced cytotoxicity through various pathways in HepG2 cells. Interestingly, when cells were exposed to SiO2 NPs for 4 h,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Some in vivo and in vitro studies have shown that SiO 2 NPs can cause toxicity to different organs in the human body; toxicity has been demonstrated in lung epithelial cells [ 9 ], liver cells [ 10 ], intestinal cells [ 11 ], the lungs [ 12 ], and kidneys [ 13 ]. In addition, SiO 2 NPs were found to induce genotoxicity and alterations in gene and protein expression [ 12 , 14 ], and Chen et al [ 15 ] reported that SiO 2 NPs can induce cornea toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Some in vivo and in vitro studies have shown that SiO 2 NPs can cause toxicity to different organs in the human body; toxicity has been demonstrated in lung epithelial cells [ 9 ], liver cells [ 10 ], intestinal cells [ 11 ], the lungs [ 12 ], and kidneys [ 13 ]. In addition, SiO 2 NPs were found to induce genotoxicity and alterations in gene and protein expression [ 12 , 14 ], and Chen et al [ 15 ] reported that SiO 2 NPs can induce cornea toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The quality control showed high quality of the data with the number of detected transcripts, proteins and phosphosites summarized in Table S1. The number of detected proteins (over 8,000) and phosphosites (over 47,000) were at the upper end of those previously reported 50,51 highlighting the improvements and breadth in coverage now possible for robust toxico-proteomic analysis.…”
Section: Quality Control Of Transcriptomics Proteomics and Phosphopro...mentioning
confidence: 66%
“…9 Also, the findings from this study are consistent with the report from Lee et al (2021) on mitochondrial effects after the exposure of HepG2 cells to a single nanosilica material and following proteomics changes. 59 Besides, mitochondrial exposure involves a relatively shorter exposure time and less material for exposure, compared with exposure of cells to these SiNPs. To our knowledge, very limited work on the application of proteomics for this purpose has thus far been done on these nanomaterials, and none on the toxicity testing of nanoforms.…”
Section: Discussionmentioning
confidence: 99%